2017
DOI: 10.1371/journal.pone.0185721
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and sequencing a Mycobacterium sp. strain F4 as a potential bioremediation agent for quinclorac

Abstract: Quinclorac is a widely used herbicide in rice filed. Unfortunately, quinclorac residues are phytotoxic to many crops/vegetables. The degradation of quinclorac in nature is very slow. On the other hand, degradation of quinclorac using bacteria can be an effective and efficient method to reduce its contamination. In this study, we isolated a quinclorac bioremediation bacterium strain F4 from quinclorac contaminated soils. Based on morphological characteristics and 16S rRNA gene sequence analysis, we identified s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Though some sequences may naturally defy the average GC skew pattern over short lengths due to functional constraints, this pattern is highly robust over extended lengths. Furthermore, the published GC skew profiles of a variety of bacterial species show numerous local GC skew inversions, suggesting that GC skew analysis can reveal a large number of natural inverted regions 32 34 . Therefore, gene inversion models are testable via the GC skew method.…”
Section: Introductionmentioning
confidence: 99%
“…Though some sequences may naturally defy the average GC skew pattern over short lengths due to functional constraints, this pattern is highly robust over extended lengths. Furthermore, the published GC skew profiles of a variety of bacterial species show numerous local GC skew inversions, suggesting that GC skew analysis can reveal a large number of natural inverted regions 32 34 . Therefore, gene inversion models are testable via the GC skew method.…”
Section: Introductionmentioning
confidence: 99%
“…70 Quinclorac is a synthetic auxin herbicide extensively used in rice fields, but the phytotoxicity of it noticeably depresses the yield and quality of crops. 77 Quinclorac is equally poisonous to tobacco seedlings when used for weed control in tobacco production. Zheng et al proved that spraying with brassinolide (75 mL/ha) reduced the inhibition rate of leaf width (decrease 9.1% and 22.9%), leaf length (decrease 1.6% and 11%), and plant height (decrease 23.8% and 0.6%) on 30-and 60-day-old subsequent tobacco by quinclorac residues from rice fields.…”
Section: Herbicide Safenersmentioning
confidence: 99%
“…Quinclorac is a synthetic auxin herbicide extensively used in rice fields, but the phytotoxicity of it noticeably depresses the yield and quality of crops . Quinclorac is equally poisonous to tobacco seedlings when used for weed control in tobacco production.…”
Section: Potential Use Of Natural Products As Herbicide Safenersmentioning
confidence: 99%
“…Li et al showed that 3-chloro-7-hydroxyquinine-8-carboxylic acid and 7-chloro-3-hydroxyquinine-8-carboxylic acid were degradation products of Mycobacterium sp. strain F4 and were nonphytotoxic to tobacco ( 19 ). Lang et al screened Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%